Surface molecular doping of all-inorganic perovskite using zethrenes molecules - Arramel (2020)
We present an optical and photoelectron spectroscopic study to elucidate the interfacial electronic properties of organic-inorganic semiconductor heterojunctions formed in a kinetically blocked heptazethrene triisopropylsilyl ethynylene (HZ-TIPS) and its homologue, octazethrene (OZ-TIPS) on an all-inorganic perovskite cesium lead bromide (CsPbBr3) surface. The photoluminescence behavior of the underlying perovskites upon differing molecular doping conditions was examined. It turns out that the charge transfer dynamics of thermally-evaporated OZ-TIPS molecule exhibited a faster average lifetime than that of the HZ-TIPS case suggesting the importance of the biradical state in the former molecule. An interfacial dipole was formed at the interface due to the competing interaction between the dispersion force of the bulky TIPS-substituent group and the attractive van der Waals interaction at the first few layers. Photoemission spectroscopy of the physisorbed HZ-TIPS shows chemical shifts, which indicates electron transfer from HZ-TIPS molecules to the CsPbBr3 perovskite single crystal. In contrast, the adsorbed OZ-TIPS molecular layer on CsPbBr3 demonstrates the opposite trend indicating a hole transfer process. The average molecular orientation as determined by near edge X-ray absorption fine structure (NEXAFS) suggests that the HZ-TIPS molecular plane is generally lifted with respect to the perovskite surface. We suggest that the nature of the closed-shell electronic ground state of HZ-TIPS could contribute to the formation of interfacial dipole at the molecule/perovskite interface.